Apical Approach Pericardiocentesis Compared to Subxiphoid Approach - Gautam, Samir; Barakoti, Murari; Dhungel, Sachin; K.C., Bishal; Hirachan, Anish; Khan, Majhar; Yadav, Umesh; Shakya, Abhishesh; Panjiyar, Rajesh; Ghimire, Jeet Prasad (Journal of National Heart and Lung Society Nepal, 2025)
Background: Very few studies have been done worldwide and no studies in Nepal to compare different approaches to pericardiocentesis. We wanted to evaluate safety and complications of apical approach pericardiocentesis. Methods: Approach to pericardiocentesis and parameters including complications noted in proforma after getting consent from the patients. This is was cross-sectional observational study. Calculation of parameters done using SPSS 20 version.Results: Total 100 patients were evaluated with 50 apical approach and 50 subxiphoid approach. Cardiac perforation, shock, hypotension and VPC noted more frequently in subxiphoid approach. No procedural death. Conclusion: Apical approach pericardiocentesis was associated with fewer complications compared to subxiphoid approach.